Antigenically related iron-regulated outer membrane proteins produced by different somatic serotypes of Pasteurella multocida. - Ikeda, J S (1988)
An 84-kilodalton outer membrane protein was expressed when Pasteurella multocida, somatic serotype 3, was grown in brain-heart infusion broth containing the iron chelator dipyridyl but not in brain-heart infusion broth alone. Antigenically related outer membrane proteins of various molecular masses were also expressed by P. multocida strains belonging to all of the other 15 somatic serotypes (somatic serotype 12 being the possible exception) as well as by isolates expressing somatic antigens representative of multiple somatic serotypes when grown under the same conditions of iron deprivation.